Prediksi Penggunaan Algoritma Iterative Dichotomiser Three Dalam Penentuan Atribut Promosi Bank Exploiset - Edy Siswanto (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2019)
In general, the Bank has many products that must be offered to customers that aim to increase profits for the bank. In this case each bank is expected to be able to maintain good relationships with existing customers so that it can facilitate the implementation of marketing related to the products of the Bank. The most frequently used effort in marketing is direct marketing or by contacting customers via telephone or e-mail, commonly referred to as telemarketing. The use of customer data is very much needed to help the bank or company make predictions about the level of success in marketing products to customers, so that it can be efficient in terms of time and also marketing costs. In this study, bank customers will be segmented in giving the right promotion using the Iterative Dichotomiser Three (ID3) method using bank telemarketing data, then processed using the RapidMiner application to get the right decision pattern in providing promotions to customers, from this analysis obtained attributes that most important in giving promotions are poutcome attributes or results from previous marketing by being influenced by several attributes including pdays, age, month, marital, day and job.